PEMBINAAN BATIK PONOROGO - FP. Sri Wuryani (Abdi Seni, 2020)
Senior High School I (SMAN  I) Ponorogo is an education institution that gives appreciation towards batik training. The activity aims to produce a batik motive design which one of them can be used as the  uniform.  Motive  of  batik  uniform  can  presents  symbolic  values  in  accordance  to  the  local character of Ponorogo and the character of correlated institution as well. By using tutorial and practical method, there can be produced some batik motives which one of them can be used as the uniform of SMAN I Ponorogo.Keywords: motive, design, batik, Ponorogo.